Contextualizing Premodern Philosophy : Explorations of the Greek, Hebrew, Arabic, and Latin Traditions. - Krause, Katja; López-Farjeat, Luis Xavier; Oschman, Nicholas A. (Milton : Taylor & Francis Group, 2022)
This volume focuses on points of interaction between discrete historical contexts, religions, and cultures found within the premodern period. The contributions connect thinkers from antiquity through the Middle Ages and include philosophers from the three major monotheistic faiths--Judaism, Islam, and Christianity.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books